PENGARUH KOMUNIKASI DAN BEBAN KERJA TERHADAP PRESTASI KERJA GURU PADA SEKOLAH MI DDI TANDASSURA KECAMATAN LIMBORO KABUPATEN POLEWALI MANDAR - Sirnan Sirnan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study aims to: 1) determine the effect of communication on teacher work performance at MI DDI Tandassura school, Limboro district, Polewali Mandar district, 2) determine the effect of workload on teacher work performance at MI DDI Tandassura school, Limboro district, Polewali Mandar district, and 3) find out which variable is more dominant in influencing teacher work performance at MI DDI Tandassura school, Limboro sub-district, Polewali Mandar district. This study uses a quantitative approach, with quantitative descriptive analysis techniques. The research was carried out for 4 months from March 2021 to June 2021. The results showed that: 1) communication had an effect on teacher performance at MI DDI Tandassura School, Limboro District, Polewali Mandar Regency, 2) Workload had no effect on teacher work performance at MI DDI Tandassura School, Limboro District, Polewali Mandar Regency. And 3) communication has a more significant effect on the Work Achievement of MI DDI Tandassura School Teachers, Limboro District, Polewali Mandar Regency.